2009
DOI: 10.1051/forest/2009063
|View full text |Cite
|
Sign up to set email alerts
|

Tree diameter, height and stocking in even-aged forests

Abstract: Keywords: monoculture / stand density index / growth model / density management diagram Abstract • Empirical observations suggest that in pure even-aged forests, the mean diameter of forest trees (D, diameter at breast height, 1.3 m above ground) tends to remain a constant proportion of stand height (H, average height of the largest trees in a stand) divided by the logarithm of stand density (N, number of trees per hectare):• Thinning causes a relatively small and temporary change in the slope β, the magnitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
(15 reference statements)
1
29
0
Order By: Relevance
“…A third parameter, which measures the rate of stand stocking, is needed to complete the description and stand density (expressed here as number of trees per hectare) is an appropriate variable to be added to the state vector. The density decrease model can be derived by using a relationship suggested in a study by Vanclay (2009), according to which the mean diameter of trees in pure even-aged forests tends to remain a constant proportion of stand height divided by the logarithm of stand density (N, trees ha -1 ):…”
Section: Density Decrease Modelmentioning
confidence: 99%
“…A third parameter, which measures the rate of stand stocking, is needed to complete the description and stand density (expressed here as number of trees per hectare) is an appropriate variable to be added to the state vector. The density decrease model can be derived by using a relationship suggested in a study by Vanclay (2009), according to which the mean diameter of trees in pure even-aged forests tends to remain a constant proportion of stand height divided by the logarithm of stand density (N, trees ha -1 ):…”
Section: Density Decrease Modelmentioning
confidence: 99%
“…As reported by Vanclay (2009), these relationships have several potential applications in the evaluation of forest resources and forest management, with the variables N, h and d being easily determined. Also, because the relationship is stable over time, it can be used to forecast future growth, to evaluate existing growth models, and, as an additional constraint in estimating simultaneous constraints, to describe tree growth.…”
Section: Discussionmentioning
confidence: 92%
“…It is related to the crown width and is a reflection of the resources potentially available to a tree. Thus (N) reflects the competition for this resource and the interaction h -ln (N) can provide a useful expression of the potential growth of individual trees (Vanclay, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports based on this trial include an examination of early growth pasture production within the Nelder plot (Lamb and Borschmann 1998;Woldring 1998), and soil and foliar analyses (Lamb and Borschmann 1998). This work showed that maple suppressed grasses more than hoop, even at relatively low densities (Costantini 1989;Woldring 1998;Xu et al 2002), and that the height-diameter-density relationship remained stable over time (Vanclay 2009). …”
Section: Literaturementioning
confidence: 91%